Molecular characterization of feline Hepatozoon species from Brazil - Rubini, A. S.; Paduan, K. D.; Perez, R. R.; Ribolla, PEM; O'Dwyer, L. H. (Elsevier B.V., 2006)
Feline Hepatozoon species from Brazil was molecular identified and characterized for the first time in São Paulo state, Brazil. Partial sequences of the 18S rRNA gene from the Hepatozoon from three naturally infected cats were analyzed. Sequences revealed that feline Hepatozoon was closely related to the canine Hepatozoon canis from Brazil. (C) 2005 Elsevier B.V All rights reserved.
Keywords: hepatozoon; feline; 18S rDNA